Young South Asian Women with ST Elevation Myocardial Infarction (STEMI)-Should we be Worried? - Rehman, Salik ur; Siddiqui, Aisha; Almas, Aysha; Khan, Aamir Hameed (Cardiology and Cardiovascular Medicine, 2022)
Background and Objective: Young women with STEMI fare worse than men. Data for such patients in particular South Asians (SA) is sparse. Therefore, this study explored the common risk factors, angiographic features and outcomes in these patients. Methods: It was a cross-sectional study done from 2013-2019 on female STEMI patients <45 years who underwent Coronary Catheterization and revascularization at Aga Khan University Hospital, Pakistan. Subjects with revascularizations or MI were excluded. Results: From a total of 1575 STEMI patients, only 26 (1.6%) were young women. Mean age was 41.2 (+3.5) years and mean BMI was 27.4 (+5.1) kg/m2. Half of the patients were diabetic (n=14) or obese (n=13). Positive family history or history of HTN was seen in a third and smoking in none. Median LDL was 135.5 mg/dl and mean total cholesterol was 203 mg/dl. More than half (56%) patients presented with Anterior STEMI and PCI was the commonest mode of revascularization. Majority, (82%, n=19) had Single vessel disease with lesions in Left Anterior Descending (LAD). Proximal LAD lesions required stents 27.6 (+10) mm long and 3.0 (+0.4) mm wide on average. Mortality was seen in one patient. A third of patients (n=9) presented with heart failure whereas a quarter (n=7) with hypotension. A minority required mechanical ventilation, Cardiopulmonary resuscitation or temporary pacemaker. Conclusions: STEMI is relatively uncommon in young SA women. Associated risk factors are Diabetes, obesity and positive family history. SVCAD with LAD involvement is the most common pattern. Rates of mortality, heart failure admissions or repeat revascularizations are minimal.